2005
DOI: 10.4067/s0365-28072005000200001
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Responses of Garlic to Temperature and Photoperiod

Abstract: 13°C) for 30 days, and later grown in a heated greenhouse with 8, 10, 12, 14 or 16 h of photoperiod. In the field, days from emergence to bulb initiation and to maturity were evaluated in 13 clones planted on six sequential planting dates. Percentage of bulbing increased and the number of days from emergence to bulb initiation decreased, as storage temperature decreased and duration of storage increased. Plants of studied clones did not form bulbs with photoperiods of 8, 10 or 12 h with any storage temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…Plants from treated cloves had better yield (clove, bulb, clove size, clove dry weight ) than plants from untreated cloves. Alejandro and Gonzalez, (2005) found that all plants of both studied clones formed bulbs when storage temperature was 4 or 7 C o . Also, linear relationships between the number of leaves and thermal time above 0 C o have been reported in garlic growing in field condition ( Buwalda ;1986,Espagnacq et al, 1987Bertoni et al,1992, Cabrera ,1993.…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…Plants from treated cloves had better yield (clove, bulb, clove size, clove dry weight ) than plants from untreated cloves. Alejandro and Gonzalez, (2005) found that all plants of both studied clones formed bulbs when storage temperature was 4 or 7 C o . Also, linear relationships between the number of leaves and thermal time above 0 C o have been reported in garlic growing in field condition ( Buwalda ;1986,Espagnacq et al, 1987Bertoni et al,1992, Cabrera ,1993.…”
Section: Introductionmentioning
confidence: 75%
“…The growth stages of A. satinum include clove sprouting , shoot growth, bulb growth and maturation (Del Pozo and Gonzalez, 2005). Clove sprouting and emergence are controlled mainly by temperature (Takagi, 1990,Barrera et al, 1998.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The bulbs were handharvested from Taşköprü district (41°30'50'' N, 34°12'53'' E, 553 m elevation), north of Turkey at the beginning of August in 2012. The bulbs were harvested at commercially mature stage according to bulbing ratios of 0.2%−0.3% and between 38% and 50% of leaves in senescence (Ledesma et al, 1997;Del Pozo and González, 2005). Harvested bulbs were fully cured under environmental conditions (35-38 °C and 45%-55% RH) in the production area for 10-12 days.…”
Section: Methodsmentioning
confidence: 99%
“…The early growth stage of garlic is suited by exposure of cloves to low temperature. Such exposure could be achieved using controlled temperature chambers such as refrigerators [ 3 ] or planting in a cool growing period, and this treatment is essential for proper development of shoot and good yield of bulb [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%